Peran Dan Kewenangan Otoritas Jasa Keuangan (OJK) Dalam Perkara Kepailitan Perusahaan Asuransi - Nurani Chofifah; Dwi Nurrahmawati; Daerent Dhavarell; Endang Kartini Panggiarti (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to find out perspectives on the role and authority of the Financial Services Authority in bankruptcy cases at insurance companies in Indonesia. OJK is an independent body that is free from government interference in its duties, functions and authority to supervise, inspect and conduct investigations in the financial services sector so as to create a good national economy. Within the scope of supervision in the insurance sector, the Financial Services Authority has the authority relating to submitting bankruptcy declaration requests to insurance companies in order to protect the interests of insurance policy holders. Arrangements regarding the authority of the Financial Services Authority in submitting requests for bankruptcy statements against insurance companies are regulated in Law no. 21 of 2011 concerning the Financial Services Authority. The research uses a qualitative descriptive approach using secondary data obtained through library research. The role of the Financial Services Authority in the bankruptcy of an insurance company is to oversee the course of the insurance company's bankruptcy until liquidation and to ensure that the insurance company has paid all its obligations to creditors.